A Translator against His will: Samir Naqqash as a Multilingual Writer in an Age of National Partitions (Jama'a: an Interdisciplinary Journal of Middle East Studies, 2020)
This article focuses on Samir Naqqash’s multilingual poetic style. It examines this style as a case study of multilingual writing in mono-national and monolingual literary realities, where there is a sharp gap between the language of the text and the expectations and lingual habits of readers. The article explores the interrelationship between languages in Naqqash’s work against the backdrop of colonial and national processes, which were dominated by linguistic and cultural partitions between Jews and Arabs, Hebrew and Arabic, and between spoken and written Arabic. It explores the extent to which Naqqash’s poetic style resists these separations, rather re-illuminating the intersections between Arabic and Hebrew, between literary and spoken language, between Islamic and Jewish traditions, and of Judeo-Arabic as a minority language in relation to the Muslim majority. Alongside the multilingual poetic model, this article examines Naqqash’s use of translation in his work; not only the translation between Arabic and Hebrew as two distinct languages, but translation as an integral part of writing and speaking. The multitude of linguistic registers in Naqqash’s writing produces multiple spaces of translation, some within the text itself, between spoken and written languages, intermingled within the text and within the language and consciousness of the speakers. Sometimes the translation occurs in the meeting point between two characters, and sometimes in the seam between the author and the text and the reader, echoing the gap between speech and writing.